2012
DOI: 10.1016/j.jus.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

US appearance of partial-thickness supraspinatus tendon tears: Application of the string theory. Pictorial essay

Abstract: The supraspinatus tendon is composed of 5 different layers consisting of intertwining bundles. On a front portion of the tendon, the layers become coated bundles which insert on the trochanter. At the insertion, the superficial or bursal surface of the tendon corresponding to the tendon fibers in contact with the subacromial bursa can be distinguished from the deep surface corresponding to the fibers in contact with the glenohumeral joint. A tendon tear may involve partial or total disruption of the tendon fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The disproportionate fluid sign is visible as a result of this. Consistent with our results, it has anecdotally been suggested that the identification of a disorder affecting the subacromial-subdeltoid bursa without intra-articular fluid collection should cause the physician to look carefully for a lesion affecting the bursal surface of the tendon (22). Therefore, given the MR findings of a near fullthickness tendon defect at the footprint and prominent subacromial-subdeltoid bursal fluid despite a lack of effusion in the glenohumeral joint, the so-called positive ''disproportionate fluid sign,'' we believe that a deep bursal-sided partial-thickness tear can easily be differentiated from a full-thickness tear.…”
Section: Discussionsupporting
confidence: 89%
“…The disproportionate fluid sign is visible as a result of this. Consistent with our results, it has anecdotally been suggested that the identification of a disorder affecting the subacromial-subdeltoid bursa without intra-articular fluid collection should cause the physician to look carefully for a lesion affecting the bursal surface of the tendon (22). Therefore, given the MR findings of a near fullthickness tendon defect at the footprint and prominent subacromial-subdeltoid bursal fluid despite a lack of effusion in the glenohumeral joint, the so-called positive ''disproportionate fluid sign,'' we believe that a deep bursal-sided partial-thickness tear can easily be differentiated from a full-thickness tear.…”
Section: Discussionsupporting
confidence: 89%
“…According to the literature, patients with only supraspinatus calcific tendinopathy were symptomatic in 6 % of the cases [8][9][10]. Patients with supraspinatus calcific tendinopathy and pain had bursitis [Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Long-axis ultrasound image of supraspinatus tendon shows bursal surface tear, filled with echoic material (arrows) and SASD bursal moderate effusion extends from the bursal (superficial) surface to the articular (deep) surface of the tendon. Partial-thickness tears of the supraspinatus tendon include lesions of only the superficial or deep surface and tendon central delamination [8]. The superficial or bursal surface tears are associated with bursitis ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An interstitial lesion is located between the two strings at the insertion. A cleavage tear is a gap running between the tendon fibers of the two strings (Figure 9, additional material) [18]. The infraspinatus muscle arises from the infraspinous fossa along the dorsal scapula.…”
Section: Rotator Cuffmentioning
confidence: 99%